Association between Abdominal Free Fluid and Postoperative Complications and Mortality in Patients with Small-Bowel Obstruction. (March 2019) - Pinar, I.; Abdul-Wahid, W.; Fransgaard, T.; Gögenur, I.
Background and Aims: Small-bowel obstruction is a frequent cause of hospitalization. The condition is potentially life-threatening, causing many admission days and is a heavy burden socioeconomically. Patients with small-bowel obstruction may develop abdominal free fluid and the quality of this fluid may be predictive of worse outcomes. Our aim was to examine whether the presence of free fluid and its density, measured on computed tomography scans, was associated with severe complications and mortality postoperatively. Materials and Methods: Patients admitted to the Department of Surgery, Zealand University Hospital with a diagnosis of small-bowel obstruction between January 2010 and December 2015 were included. Medical records were reviewed and preoperative computed tomography scans were examined. A radiologist blinded to the outcomes reviewed all Hounsfield unit values of the free fluid. The primary outcomes evaluated were odds ratios of the severity of complications and hazard ratios of 30- and 90-day mortality postoperatively. Results: A total of 289 patients were included. Analyses revealed an adjusted odds ratio of 1.03 (95%confidence interval = 0.93–1.15) between the presence of free fluid and postoperative complications and an adjusted hazard ratio of 1.28 (95% confidence interval =  0.80–2.05, p  = 0.30) of the 30-day mortality in this patient group. Furthermore, the analyses revealed an adjusted odds ratio of 1.22 (95% confidence interval 0.98–1.52) between the density of the free fluid > 20 Hounsfield unit and postoperative complications and an adjusted hazard ratio of 0.85 (95% confidence interval =  0.28–2.63, p  = 0.78) of the 30-day mortality. Conclusion: No significant correlation was found between the presence of free fluid nor its density in regard to postoperative complications or mortality in patients with small-bowel obstruction.